"Better safe than sorry": a qualitative content analysis of participant's perspectives of fall-related concerns and balance in older women with osteoporosis after balance training. Issue 8 (9th April 2016) - Halvarsson, Alexandra; Ståhle, Agneta; Halén, Carolina; Roaldsen, Kirsti Skavberg
Abstract: Purpose : To explore how older women with osteoporosis perceive fall-related concerns and balance in daily life after having participated in balance training. Methods : Explorative study. Semi-structured interviews were conducted with 19 women (66–84 years), with osteoporosis recruited from an ongoing RCT; participants were asked about their perceived fall-related concerns and balance. Interviews were taped and transcribed verbatim. Data were analyzed using inductive qualitative content analysis. Results : One underlying theme emerged: "Internalized risk perception related to experience of bodily fragility", and three manifest categories: empowerment, safety and menace. A dynamic process between the categories was found, in which contextual and personal factors influenced perceptions of fall-related concerns and balance, i.e. winter season may lead a person who is highly empowered and/or uses active strategies into a situation of perception of menace and avoidance of activity. Conclusion : To cope with the fragility caused by osteoporosis informants had an internalized risk perception that protected them against possible threats and harm. Informants perceived improved empowerment and self-efficacy after participation in balance training. They resumed activities and became more active and independent in daily life using safety precautions and fall-prevention strategies. Depending on contextual factors, some situations still invoked fear and led to avoidance. Implication for Rehabilitation: Risk awareness protecting against possible threats and harms seems to be internalized in older women living with osteoporosis. When designing fall prevention programs, it is important to recognize that contextual and personal factors have a major influence on how older women with osteoporosis perceive fall-related concerns and balance. Perception of fragility and risk seems to be a significant problem for older women with osteoporosis and health-care providers should encourage their patients to participate in tailored balance training programs to overcome these concerns.